2004
DOI: 10.1136/aim.22.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Low Back Pain in Pregnancy – a Prospective, Quasi- Randomised, Controlled Study

Abstract: This study was undertaken to investigate the effects of acupuncture in low back and pelvic pain during pregnancy under real life conditions, as compared with patients undergoing conventional treatment alone. A total of 61 conventionally treated pregnant women were allocated randomly into two groups to be treated or not by acupuncture. Twenty-seven patients formed the study group and 34 the control group. They reported the severity of pain using a Numerical Rating Scale from 0 to 10, and their capacity to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 29 publications
2
60
0
4
Order By: Relevance
“…[28][29][30][31][32][33] To date, two rigorously conducted systematic reviews have been published. 7,34 The first of these was a Cochrane Review of eight studies (1305 participants) testing the effects of adding various pregnancy-specific exercises, physiotherapy, acupuncture and pillows to standard pre-natal care.…”
Section: Acupuncturementioning
confidence: 99%
“…[28][29][30][31][32][33] To date, two rigorously conducted systematic reviews have been published. 7,34 The first of these was a Cochrane Review of eight studies (1305 participants) testing the effects of adding various pregnancy-specific exercises, physiotherapy, acupuncture and pillows to standard pre-natal care.…”
Section: Acupuncturementioning
confidence: 99%
“…In a study on the most common non-obstetric complaints reported by Brazilian pregnant women, Guerreiro da Silva found that 30% of them experienced sleep disturbances [20], 56% anxiety [21], and 77% low back pain [22]. Although these symptoms are extremely common during pregnancy, they are often neglected by physicians during prenatal care, as most drugs available for their management are of questionable safety (pregnancy category C) or pose a risk to the fetus (pregnancy category D).…”
mentioning
confidence: 99%
“…Water gymnastics [35] and yoga [83] were also found to be effective in reducing pain intensity. Two case reports [84,85] and 6 RCTs studied the role of acupuncture [22,32,33,36,86,87] . Two of these RCTs demonstrated analgesic benefit when compared to controls [22,36] .…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…Two case reports [84,85] and 6 RCTs studied the role of acupuncture [22,32,33,36,86,87] . Two of these RCTs demonstrated analgesic benefit when compared to controls [22,36] . Acupuncture, as an adjunct to standard treatment, was found to be better than standard treatment alone for reduction of pain and improving the ability to perform daily activities in pregnancy-related PGP [32,33] .…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
See 1 more Smart Citation